PREVENTIF COVID-19 BERBASIS PENYULUHAN TERHADAP SANTRI DI PONDOK PESANTREN KARANG KADEMPEL SEBAGAI WUJUD IMPLEMENTASI PENGALAMAN BELAJAR LAPANGAN - Wibowo, Pipid Ari; Abidin, Zaenal; Nugrahani, Wulan; Fahrum, Anastita Amaliya; Nurannisa, Fitri Revita (Jurnal Pengabdian Dharma Bakti, 2021)
Often times, the prevention and control of Covid-19 in Islamic boarding schools is overlooked, even though if one is confirmed positive, the spread is very difficult to contain. It was recorded that until the end of 2020, 1700 students in 32 Indonesian Islamic boarding schools were exposed to Covid. Many efforts have been made to reduce cases of the corona virus in Indonesia, especially in Islamic boarding schools. One of them is by involving education and health institutions, in providing information through the media to conducting community service in the form of counseling at Islamic boarding schools. The purpose of this community service activity is to increase knowledge and application of Santri at the Karang Kadempel Jiwan Islamic Boarding School, related to prevention and overcoming Covid-19 in the cottage environment. The method used in this activity is in the form of learning by doing about the implementation of the 3M health protocol and 6 steps to wash hands with soap (CTPS) properly. The result of this community service activity is an increase in the knowledge and understanding of students regarding the prevention of Covid in the cottage environment, as an effort to defend themselves in the midst of an outbreak that is currently raging.Keywords : Preventive Covid-19, counseling, Islamic boarding schools